Positionality Memo - Rojo, Florencia (TRAILS: Teaching Resources and Innovations Library for Sociology, 2023)
This assignment aims at developing students’ analytic perspectives about how identities and social location within systems of power shape community-engaged research. Students are typically practiced at identifying and acknowledging their various identities relating to race, class, gender, sexuality, and other forms of difference. Many students also have experience considering how their identities have shaped their lives through practices, such as writing college admission essays about overcoming hardships. The positionality memo assignment takes this line of inquiry further. This assignment was designed for a project-based, community-engaged learning course and asks students to think about their positionality in the applied work they are completing for class. Effective community-engaged learning depends on students having a robust sociological imagination, and “sociologically uninformed” community engagement can lead to students objectifying, stereotyping, and condescending community partners. Therefore, students are expected to not only describe but also make a plan for accounting for their positionality in the field and in their project outcomes.